Air Transport and Sustainable Development: What Complementarities and Compatibility for the Future? (Global Journal of Human-Social Science, 2012)
History is replete of its own repetitions and contradictions and domestic and international air transport are no exceptions It has now become necessary for several reasons to assess how limited resources could be more wisely used for further welfare and economic growth without threatening the very existence of mankind In other words we need to stop shooting ourselves in the foot by playing a game of duplicity when it comes to ecology and environmental protection the paradox of economic development and industrialization The 20th century has seen the rapid and swift development of both international and domestic air transport worldwide Emphases then were on efficiency speed comfort cabin and cargo space and load factor In the 2nd half of the last century more specifically in the early 70s up to the end of the century and as a result of energy crises oil peaks and price hikes of cartels more attention was given to fuel efficiency Air transport being an essential service has forced most aircraft manufacturers to devote more energy investment and time to designing better equipment In so doing aircraft manufacturers airline operators and governments have all overlooked the issue of sustainability This oversight has now become a major concern for all Because of the global but fragmented nature of air transport it is difficult to regulate the industry in order to establish standard policies and procedures Attempts made by the European Union have so far produced mitigated results In this paper we look at the contradictions and paradoxes when nations have to make a choice between the now and the future between the options of further economic growth and sustainability and between welfare and wealth
Keywords: International and domestic air transport; sustainability; policies; carbon emissions